Revisiting lip shave: a solution for disorders of the vermilion border. Issue 1 (January 2018) - Sayan, A.; Wijesinghe, S.; Paraneetharan, S.; Ilankovan, V.
Abstract: Actinic keratosis, leukoplakia, carcinoma in situ, and superficially invasive carcinomas of the lower lip are caused mainly by the cumulative effects of exposure of the vermilion of the lower lip to ultraviolet radiation. Current treatments all have limitations: cryosurgery or electrosurgery is suitable to treat only focal lesions; topical chemotherapy, which is an option for diffuse actinic damage, yields unreliable results; and laser treatment fails to rejuvenate the vermilion. However, "lip shave", which involves full-thickness excision of the damaged vermilion and reconstruction with an advancement labial mucosal flap, will produce a fresh mucosal lining to the vermilion border. We describe our experience of the technique and evaluate the functional and aesthetic outcomes in 20 patients treated between January 2011 and January 2016. The follow-up period ranged from 24 to 60 months. Three-quarters of the patients had dysplasia or superficially invasive malignancy. Resected lesions were about 63 mm long, 13.7 mm wide, and 3.9 mm deep. No patients had recurrence or secondary lesions during follow up, functional disturbance was minimal, and the cosmetic outcome pleasing. Lip shave can efficiently reconstruct the vermilion of the lower lip with minimum deformity.